Brevibacillus brevis HNCS-1: a biocontrol bacterium against tea plant diseases - Yang, Wenbo; Yang, Hui; Bao, Xiaocun; Hussain, Mehboob; Bao, Qiang; Zeng, Zexuan; Xiao, Chun; Zhou, Lingyun; Qin, Xiaoping (Frontiers in Microbiology, 2023)
As a biocontrol bacteria, Brevibacillus has been the subject of extensive research for agricultural applications. Antibacterial peptides (AMPs) are the main antibacterial products of Brevibacillus. This study isolated a strain of Br. brevis HNCS-1 from tea garden soil, and the strain has an antagonistic effect against five types of pathogens of tea diseases, namely Gloeosporium theae-sinensis, Elsinoe leucospira, Phyllosticta theaefolia, Fusarium sp., and Cercospora theae. To determine the genetic characteristics implicated in the biocontrol mechanism, the genome sequence of the HNCS-1 strain was obtained and analyzed further, and the data are deposited in the GenBank repository (No. CP128411). Comparative genomics analyses revealed that the HNCS-1 strain and 17 public Br. brevis share a core genome composed of 3,742 genes. Interestingly, only one non-ribosomal peptide synthetase (NRPS) gene cluster annotated as edeine is present in the core genome. And UHPLC-MS/MS detection results showd that edeine B and edeine A were the principal antibacterial peptides in the HNCS-1 strain. This study proves that edeine is the main antibacterial peptide of Br. brevis, and provides a new strategy for the identification of antibacterial products from other biocontrol bacteria.